Metaphorical Expression in the Song Lyrics of Album Evermore by Taylor Swift - Waladdin Panggabean; Nofansyah Nofansyah (Hasanuddin University, 2024)
This study aims to identify the metaphorical terms included in the lyrics of Taylor Swift's album